2013
DOI: 10.1371/journal.pone.0082163
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Crown-Like Structure: A Unique Histological Feature in Non-Alcoholic Steatohepatitis in Mice and Humans

Abstract: Although macrophages are thought to be crucial for the pathogenesis of chronic inflammatory diseases, how they are involved in disease progression from simple steatosis to non-alcoholic steatohepatitis (NASH) is poorly understood. Here we report the unique histological structure termed “hepatic crown-like structures (hCLS)” in the mouse model of human NASH; melanocortin-4 receptor deficient mice fed a Western diet. In hCLS, CD11c-positive macrophages aggregate to surround hepatocytes with large lipid droplets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
184
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(204 citation statements)
references
References 51 publications
18
184
0
2
Order By: Relevance
“…The data of this study suggest that CLS is an important origin of fibrosis as well as inflammation in adipose tissue. This notion is supported by our recent observations that the CLS-like histological structure in the liver of nonalcoholic steatohepatitis in mice and humans, which may be involved in the fibrogenesis of the liver 26 . Given that Mincle expression is localized to macrophages constituting CLS and that residual lipid droplets of dead adipocytes are scavenged by macrophages within CLS, Mincle can sense as-yet-unidentified endogenous ligands that are released as danger signals from dead adipocytes in the ARTICLE interaction between adipocytes and macrophages.…”
Section: Discussionsupporting
confidence: 70%
“…The data of this study suggest that CLS is an important origin of fibrosis as well as inflammation in adipose tissue. This notion is supported by our recent observations that the CLS-like histological structure in the liver of nonalcoholic steatohepatitis in mice and humans, which may be involved in the fibrogenesis of the liver 26 . Given that Mincle expression is localized to macrophages constituting CLS and that residual lipid droplets of dead adipocytes are scavenged by macrophages within CLS, Mincle can sense as-yet-unidentified endogenous ligands that are released as danger signals from dead adipocytes in the ARTICLE interaction between adipocytes and macrophages.…”
Section: Discussionsupporting
confidence: 70%
“…We found bizarre microstructures in livers from MC4R-KO mice, which are very similar to CLS in obese adipose tissue [ 7 ]. We have called them "hepatic crown-like structures" (hCLS), where macrophages aggregate to surround hepatocytes with large lipid droplets.…”
Section: Identifi Cation Of Hepatic Crown-like Structure (Hcls)mentioning
confidence: 73%
“…In the NASH liver, macrophages can interact with and engulf dead hepatocytes within hCLS, thereby activating fi brogenic cells to stimulate hepatic fi brosis as an adaptive repair response to tissue injury. It is, therefore, likely that hCLS serves as an origin of hepatic infl ammation and fi brosis during the progression from simple steatosis to NASH [ 7 ].…”
Section: Identifi Cation Of Hepatic Crown-like Structure (Hcls)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has recently been reported that breast WAT from Black women, who have worse prognosis with breast cancer, have higher density of CLS-B than their non-Black counterparts (22). The probability that WAT inflammation helps to explain the obesity-inflammation-carcinogenesis axis is further supported by observations showing the occurrence of CLS in adipose tissue associated with other malignancies, including oral squamous cell carcinoma of the tongue (23), endometrial cancer (24), and in the report of liver macrophages, identified as Kupffer cells, forming CLS with lipidladen hepatocytes in NAFLD, a disorder now considered to be a precursor for hepatocellular cancer (14,25).…”
Section: Articles By Iyengar Et Al Published In This Issue Cancer Prmentioning
confidence: 85%